Clinically Significant Improvement in a Case of Bronchial Asthma with Unani Medicine: A Case Report - Yasmeen Shamsi; Rabia Khan; Sadia Nikhat (Tehran University of Medical Sciences, 2019)
Asthma is known by various terms as ḍīq al nafs, ribw, boḩr and dama in Unani system of medicine. It is a chronic inflammatory paroxysmal disease characterized by spastic contraction of smooth muscles in bronchioles, which can cause extreme difficulty in breathing. According to the Global Asthma Report 2018, about 6% of children and 2% of adults in India are known to be living with asthma. Herein we describe a case of bronchial asthma which was successfully treated with Unani medicines. The patient was a 21 year old male, suffering from asthma for 19 years but without any co-morbidity. He was prescribed bronchodilator, anti-inflammatory and anti-spasmodic Unani drugs such as tukhm khaṭmī (Althaea officinalis Linn. seed), tukhm khubbāzī (Malva sylvestris Linn. seed), aşl-us-sūs muqashshar (Glycyrrhiza glabra Linn., peeled root), parsiāoshān (Adiantum capillus-veneris Linn.) etc. in crude form as decoction. He was symptom free and medication free after 2 months of treatment till he last reported in April 2019. The results are attributed to the herbal drugs which not only provide symptom relief but also correct the airway hyper-responsiveness and correct the histopathological changes induced by asthma.